Building Macro SAMs from Cross-Country Databases : Method and Matrices for 133 Countries - Cicowiez, Martín (2017)
Social accounting matrices (SAMs) are the key data input for computable general equilibrium (CGE) models. After a brief introduction to SAMs, this paper presents a method and related computer program for constructing macro SAMs from cross-country databases. The method is demonstrated in an appendix where it is used to build such a SAM for Guinea in Excel. With the help of the program, macro SAMs were built for 133 countries, including many low-income and/or fragile countries. The SAMs and the code for the program are available in electronic form. A companion paper presents a CGE model with a user-friendly interface for which such SAMs provide the bulk of the data needed for macro applications.